2018
DOI: 10.21037/atm.2018.01.25
|View full text |Cite
|
Sign up to set email alerts
|

The role of positron emission tomography in the diagnosis, staging and response assessment of non-small cell lung cancer

Abstract: Lung cancer is a common disease and the leading cause of cancer-related mortality, with non-small cell lung cancer (NSCLC) accounting for the majority of cases. Following diagnosis of lung cancer, accurate staging is essential to guide clinical management and inform prognosis. Positron emission tomography (PET) in conjunction with computed tomography (CT)-as PET-CT has developed as an important tool in the multi-disciplinary management of lung cancer. This article will review the current evidence for the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 71 publications
1
55
0
1
Order By: Relevance
“…Four cases of our study showed changing in their TNM staging due to the difference in diagnosis of the nature of pulmonary nodules. The ability of PET/CT to differentiate the benign from the malignant nodules affects both T and M staging, and this is consistent with Volpi et al who discussed the accuracy of PET/CT in differentiating the benign nodules from a malignant one [6].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Four cases of our study showed changing in their TNM staging due to the difference in diagnosis of the nature of pulmonary nodules. The ability of PET/CT to differentiate the benign from the malignant nodules affects both T and M staging, and this is consistent with Volpi et al who discussed the accuracy of PET/CT in differentiating the benign nodules from a malignant one [6].…”
Section: Discussionsupporting
confidence: 85%
“…PET/CT is a known modality to detect the malignant activity in the mediastinal lymph nodes more accurately compared to the CT which depends only on the nodal size with the accuracy reaching to about 90% in the diagnosis of malignant mediastinal lymphadenopathy [6,11,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the fluorine inhibits the cell from metabolizing phosphorylated FDG past this step [3][4][5]. PET imaging is then able to detect the radioisotopic fluorine accumulating in tissues [2,6]. As one of the hallmarks of cancer is increased glucose metabolism, this procedure allows for diagnostic imaging in cancer patients [7,8].…”
Section: Glycolytic Shift In Tumor Cellsmentioning
confidence: 99%